Co-occurrence of Alzheimer’s disease β-amyloid and tau pathologies at synapses - Takahashi, Reisuke H. (2008)
Although β-amyloid (Aβ) plaques and tau neurofibrillary tangles are hallmarks of Alzheimer’s disease (AD) neuropathology, loss of synapses is considered the best correlate of cognitive decline in AD, rather than plaques or tangles. How pathological Aβ and tau aggregation relate to each other and to alterations in synapses remains unclear. Since aberrant tau phosphorylation occurs in amyloid precursor protein (APP) Swedish mutant transgenic mice, and since neurofibrillary tangles develop in triple transgenic mice harboring mutations in APP, tau and presenilin 1, we utilized these well-characterized mouse models to explore the relation between Aβ and tau pathologies. We now report that pathological accumulation of Aβ and hyperphosphorylation of tau develop concomitantly within synaptic terminals.